The Enhancement of Learning English Vocabulary Through Hangman Game: A Case Studyof Sixth Year Students At Pakou Secondary School - PANFONGPHET, Sipaseuth; VANDALAK, Phonesavanh; YONGTONG, Khamlavang; PHOMMANEESONE, Souksavanh; KEOPASITH, Vathsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research aimed to study on improving students’ learning English vocabulary among the sixth year students at Pakou secondary school. The objectives are to find out how Hangman Game can improve the sixth year students in learning English vocabulary and to study the students’ satisfaction towards the use of Hangman Game the in learning English vocabulary at Pakou Secondary School. The sample group of research consisted of 31 students, 16 males and 15 females who were studying in year six, at Pakou secondary school by using lucky draw method from classes. The equipment of research composed of the test form for learning achievement which include four multiple choice questions in 20 questionnaires. There are implementation and behavior evaluation forms consist of 15 questionnaires for satisfaction evaluation. Data was collected through pre-test, post- test and questionnaires for satisfaction evaluation and the Program SPSS (Statistical Package Social Science version 24) was deployed to analyze the pre-test, post-test and the questionnaires. The results of research clearly shown as followed: 1) Hangman Game can improve students in learning English vocabulary and motivate the fifth year students at Pakou secondary school is total 0.97 or 97.00%. 2) The students satisfied teaching and learning English vocabulary by using Hangman Game which was created to develop students in learning English vocabulary, and students were satisfied in high level.